Reliability and validity of a taekwondo electronic body protector / Ryan Chong Wy Lunn - Ryan Chong , Wy Lunn (2018)
Protector and Scoring System (PSS) was introduced in Taekwondo to encourage transparency in scoring during competition and has been used in the Olympics since London 2012. It consists of two main components which are the electronic body protector and electronic socks. There have been limited number of studies done on the PSS, nearly all of the previous studies were not comprehensive and had questionable testing methods. Therefore the main objective of this study was to methodologically examine the validity and reliability of the PSS. To fulfill these objectives, a custom made mechanical pendulum was built to test the PSS. The reliability of the pendulum was first determined by tracking the pendulum’s mean velocity at impact on two separate occasions. The kinetic energy of the pendulum was then calculated on average to be 55.52 Joules. For the experimental trial, the electronic body protector was divided into 12 sections and each section was tested with 50 trials on two separate days. It was found that only three sections had no significant differences (p > 0.01) between the two days while the rest of the sections had significantly different reading between day one and day two. Based on the homologous descriptive statistic, only two sections were in the same group which translates to the PSS being only 16.7% reliable overall over both days. In terms of validity, t-test was used to measure the differences between the calculated kinetic energy from the pendulum and the displayed kinetic energy on the PSS; values were found to be significantly different (p < 0.01). Overall, the PSS was found to be neither reliable nor a valid scoring tool. It is suggested that each unit should also be examined and scrutinized prior to being used in any future tournaments.